RLMD-PA: A Reinforcement Learning-Based Myocarditis Diagnosis Combined with a Population-Based Algorithm for Pretraining Weights - Seyed Vahid Moravvej; Roohallah Alizadehsani; Sadia Khanam; Zahra Sobhaninia; Afshin Shoeibi; Fahime Khozeimeh; Zahra Alizadeh Sani; Ru-San Tan; Abbas Khosravi; Saeid Nahavandi; Nahrizul Adib Kadri; N. Arunkumar; et al. (WILEY - HINDAWI, 2024)
Indexed by WOS/SCOPUS/ERA